Comorbidities and medication use in patients with a recent clinical fracture at the Fracture Liaison Service. Issue 2 (February 2018) - Vranken, L.; Wyers, C.; Velde, R.; Janzing, H.; Kaarsemaker, S.; Geusens, P.; Bergh, J.
Abstract Summary In this cross-sectional study, two-thirds of Fracture Liaison Service (FLS) patients had comorbidities and medications associated with increased bone- or fall-related fracture risk. Bone-related and fall-related fracture risk (BRR and FRR) were associated with age and fracture type, but not with gender or BMD. Systematic evaluation of these factors leads to a more profound assessment in FLS care. Introduction This study is a systematic evaluation of comorbidities and medications associated with increased fracture risk in patients aged 50–90 years with a recent fracture visiting the FLS. Methods In this cross-sectional cohort study, comorbidities were classified according to ICD-10 and medications according to the Anatomic Therapeutic Chemical (ATC) classification and further categorized into those associated BRR and FRR. Results Of 1282 patients (72% women; 65 ± 9 years), 53% had at least one BRR, 46% had at least one FRR, and 66% at least one BRR and/or FRR. At least one BRR, as well as at least one FRR were associated with age, BMI, and fracture type, but not with gender or BMD. The proportion of patients with only BRR (± 20%) or only FRR (± 10%) was similar among ages, gender, BMI, fracture type, and BMD. The combination of at least one BRR and at least one FRR was significantly associated with age, BMI, and major fractures, but not with gender or BMD. Conclusion Comorbidities and medications associated with increased fracture risk are present in two-thirds of patients visiting the FLS. In addition, the proportion of patients having a combination of BRR and FRR increased significantly with age, BMI, and fracture severity. This indicates that systematic evaluation of these factors is important for a more profound assessment of subsequent fracture risk in FLS care.